Teachers' and students' perceptions on the implementation of the Cambridge curriculum in English subject - Sima Nisbatin Niswa; Khusnul Harsul Lisan; Satwika Nindya Kirana (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2024)
This study aimed to describe the teachers' and students' perceptions of the implementation of the Cambridge curriculum in English subjects along with the obstacles experienced and alternative solutions to these obstacles. This study used a qualitative method with a case study approach. This research was carried out in the following stages: initial research and data collection, transcription of conversations and interview results, data analysis, and reports.Data collection techniques in this study were observation, interviews, and documentation, with research subjects consisting of eight students, two Madrasah Tsanawiyah (MTs) English teachers, and one representative from Assalafiyyah Language Center (ALC) who oversaw the implementation of the Cambridge Curriculum at MTs Assalafiyyah.To analyze the data, this research used Miles and Hubbermans cycle. The results of the study show that teachers and students have positive and welcoming perceptions of the implementation of the Cambridge curriculum at MTs Assalafiyyah.However, there were obstacles experienced related to delivery, the materials, and the facilities. Then the proposed alternative solutions can be implemented by increasing teacher training, giving students opportunities for extensive learning, and providing some required facilities to maximize the implementation of the Cambridge curriculum in MTs Assalafiyyah.